Diagnostics of deuterium gas-puff z-pinch experiments on the GIT-12 generator; Bulletin of the American Physical Society; Vol. 59, № 15 : 56th Annual Meeting of the APS Division of Plasma Physics, Monday–Friday, October 27–31, 2014, New Orleans, Louisiana - Cikhardt J.; Klir D.; Rezac K.; Kubes P.; Kravarik J.; Batobolotova B.; Sila O.; Turek K.; Shishlov A.; Labetsky A.; Kokshenev V.; Chedizov R.; et al. (2014, 2014)
Title screen